A dynamic Cassie–Baxter model1. Issue 8 (28th February 2015) - Liu, Tingyi Leo; Chen, Zhiyu; Kim, Chang-Jin
<x xml:space="preserve">Abstract</x> A new model predicts the receding contact angle of a liquid suspended on microstructures for a wide range of data in the literature regardless of their distinct patterns and receding modes.